Análisis de factibilidad para implementar una maquina de pañales - Idrovo, Mayra (2009)
By the end of 2008 a crisis at world-wide level appeared product of different factors economic, political like the reduction of price like the petroleum, completion of commercial relations between several countries. Due to this world-wide each country we look for alternatives to safeguard the internal economy, development of plans and policies. After reaching an agreement with the industrialists, the Government of Ecuador announced the restriction of a series of importations concerned like a measurement to palliate the effects of world-wide financial crisis. One of the businesses that were affected by this type of measures is the sector of personal care. The unique option to the supply articles of that type, is that the national production compensates 30% of the total production. In the case of the disposable diapers Guayaquil buys 37.1% of the existing supply in the country. Based on that the opportunity of growth in sales and benefits for the companies established in Ecuador for year 2009 will be in risk because there is no opportunity to compete with the prices and the required volumes.